2013
DOI: 10.1080/08870446.2012.723711
|View full text |Cite
|
Sign up to set email alerts
|

The effect of implementation intentions on physical activity among obese older adults: A randomised control study

Abstract: RESULTS suggest that IIs could be appropriate to favour the maintenance of physical activity among inactive obese older adults. However, this technique seems to have limited impacts over and above common intervention activities on weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Moreover, relating our findings to the meta-analytic result for implementation intentions on health behavior by Gollwitzer and Sheeran (2006;d ϭ .59 [k ϭ 23]), our effect displays a similar strength. This is only the fourth study to investigate and reveal this effect of the implementation intention strategy on a real-life prospective memory task in old age, and therefore in concert with the previous studies (Bélanger-Gravel et al, 2013;Brom et al, 2013;Liu & Park, 2004) allowing a more generalized conclusion on the efficiency of the implementation intention strategy for older adults.…”
Section: Reducing Prospective Memory Task Demands: Strategy Trainingmentioning
confidence: 86%
“…Moreover, relating our findings to the meta-analytic result for implementation intentions on health behavior by Gollwitzer and Sheeran (2006;d ϭ .59 [k ϭ 23]), our effect displays a similar strength. This is only the fourth study to investigate and reveal this effect of the implementation intention strategy on a real-life prospective memory task in old age, and therefore in concert with the previous studies (Bélanger-Gravel et al, 2013;Brom et al, 2013;Liu & Park, 2004) allowing a more generalized conclusion on the efficiency of the implementation intention strategy for older adults.…”
Section: Reducing Prospective Memory Task Demands: Strategy Trainingmentioning
confidence: 86%
“…Of these, 18 articles concerned 15 studies with a patient population and stated that an implementation intention had been used [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two articles were excluded as they described the development of an intervention, an RCT protocol and its feasibility testing [63,64].…”
Section: Resultsmentioning
confidence: 99%
“…The four included studies (reported in five articles) concerned the evaluation of the effectiveness of an if-then plan on i) medication adherence in epilepsy [51] and stroke [53,65], ii) improving exercising and behavioural change in people with chronic back [60], and iii) improving physical activity in obese older adults [66]. Table 2 outlines a summary of the interventions employed in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations